Inovasi Metode Pembelajaran Pendidikan Pancasila di Era Digital - Elhaj Nadhif Lukman; Prawira Hadiwijaya; Syahkir Rifaldy; Adrian Juliansyah Rahmat; Herli Antoni (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Pancasila education as a fundamental subject in shaping the nation's character needs to be adapted to technological developments in the digital era. Innovative learning methods that utilize information and communication technology can increase the effectiveness of learning and the relevance of Pancasila values for the younger generation. This journal discusses various innovations in learning methods that can be applied in Pancasila education, the challenges faced, and their impact on the understanding and application of Pancasila values among students.